'Talking Itself Out of a Political Future': Education and Australian Army Engagement with Papua New Guinean Independence, 1966–72. Issue 2 (3rd April 2019) - Moss, Tristan
ABSTRACT: The Australian Army, while having a long association with Papua New Guinea after the Second World War and before independence in 1975, is often conceptualized as a small player in the decolonization process, of interest to scholars because of its cost and potential threat to democratic government. This article examines the Army's education programme and associated policies in the decade before independence to argue that the institution was acutely aware of looming decolonization, and actively sought to create a national Papua New Guinean military by repurposing policies originally designed to serve Australia's defence needs, in particular through 'civic' education. It embarked on this path without direction from the Department of Territories. While the results of 'civic' education are difficult to determine, this article shows that the Australian Army was engaged in the profound shifts occurring around it in Papua New Guinea.